2018
DOI: 10.1103/physrevb.97.121201
|View full text |Cite
|
Sign up to set email alerts
|

Towards predictive many-body calculations of phonon-limited carrier mobilities in semiconductors

Abstract: We probe the accuracy limit of ab initio calculations of carrier mobilities in semiconductors, within the framework of the Boltzmann transport equation. By focusing on the paradigmatic case of silicon, we show that fully predictive calculations of electron and hole mobilities require many-body quasiparticle corrections to band structures and electron-phonon matrix elements, the inclusion of spin-orbit coupling, and an extremely fine sampling of inelastic scattering processes in momentum space. By considering a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
348
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(373 citation statements)
references
References 65 publications
22
348
2
1
Order By: Relevance
“…As the total decay rate is also equal to twice the negative imaginary part of the retarded electron self-energy, this approximation has been referred to as the self-energy relaxation time approximation (SERTA) [55]. Similar to the case of the MRTA, the linear response coefficients in the SERTA are given by…”
Section: Approximations To the Boltzmann Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the total decay rate is also equal to twice the negative imaginary part of the retarded electron self-energy, this approximation has been referred to as the self-energy relaxation time approximation (SERTA) [55]. Similar to the case of the MRTA, the linear response coefficients in the SERTA are given by…”
Section: Approximations To the Boltzmann Equationmentioning
confidence: 99%
“…8. Finally, these ab initio calculations [55,140] revealed that acoustic-phonon scattering in silicon is much more important than previously thought [141].…”
Section: 11mentioning
confidence: 99%
“…In the self-energy relaxation time approximation (SERTA) 64 , the electron carrier mobility takes the simple form…”
Section: Methodsmentioning
confidence: 99%
“…Parameters: 21 × 21 k points (135 × 135 k for the pristine DOS), 60 bands, and η = 5 meV (20 meV in the bands).are no bound states in the bands), but a dense k-point grid(135 × 135) in order to sample the constant-energy surface on which the quasiparticle scattering takes place. In the case of graphene, quasibound resonant states are inherent to the Dirac cone dispersion, and hence both the the resonant state and the scattering rate can be calculated with a dense k-point sampling including only a few bands.With the above-mentioned number of bands and kpoint samplings, the dimension M of the matrices in Eqs (43). becomes M = N b × N k ∼ 20.000-50.000.…”
mentioning
confidence: 99%